Correlation between Clinical Presentation and Confirmation of Female Genital TB among Infertility Patients - Zahan, Rezoana Refat; Sultana, Nilufar; Afroj, Sultana; MD. Shakil, Abu Toha; Paul, Ratna (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Female genital tuberculosis (FGTB) is a Mycobacterium infection in the female reproductive organ which may be a cause of female infertility. The prevalence of pulmonary TB in Bangladesh is high whereas prevalence of extra-pulmonary tuberculosis such as Female Genital Tuberculosis (FGTB) affecting infertility is unknown. Diagnosis of FGTB is difficult.Early detection of the disease can prevent irreversible damage to the reproductive system and can prevent fertility complication. Methods: This cross-sectional observational study was done with an aim to find out the correlation of presenting symptoms with the confirmatory findings of FGTB among 60 infertility patients from July 2020 to June 2021 in Reproductive Endocrinology & Infertility Unit, Dhaka Medical College Hospital, Dhaka, Bangladesh. Results: Our study cases were 60. Among them 11.67% patients was found TB-PCR positive and 1.67% was found histopathologically positive. Among the confirmed cases 62.5% had chronic pelvic pain,50% had menstrual disorder, 12.5% had pelvic mass and 12.5% was asymptomatic except infertility. In histopathology/TB-PCR positive group 4(50%) patients had cornual block in their HSG but in histopathology/TB-PCR negative group 13(25%) patient had cornual block. The difference was statistically significant ( p< 0.05) between two groups. Conclusion: Infertile patients who live in countries where Tuberculosis is an endemic disease like Bangladesh, a comprehensive history taking along with USG, HSG and laparoscopy findings can be used to diagnose FGTB. Confirmation can be achieved through AFB smear, TB-PCR and histopathological results. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(1): 30-35